Topographic correlation of microperimetry with foveal microstructure characteristics in idiopathic epiretinal membrane patients with an ectopic inner foveal layer - Qianqian Wang; Congyao Wang; Yihua Su; Fenfen Yu; Tingting Chen; Xia Dong; Pengxia Wan (Eye and Vision)
Abstract Purpose To identify foveal structure-function topographic association and relationship in patients with idiopathic epiretinal membrane (ERM) related to ectopic inner foveal layer (EIFL). Methods This was a cross-sectional, observational study that involved 40 individuals with idiopathic ERM: 22 without EIFL (Group 1) and 18 with EIFL (Group 2). Quantitative foveal light sensitivity was measured using microperimetry, and foveal microstructure was assessed using spectral-domain optical coherence tomography (SD-OCT) and optical coherence tomography angiography (OCTA). Multiple indices of microvascular parameters of OCTA images were further processed using the AngioTool software. LASSO regression and quantile regression analyses were performed to identify the spatial distribution correlation between foveal light sensitivity and foveal microstructure parameters. Results Group 2 exhibited reduced light sensitivity across all parameters of microperimetry compared to Group 1 (P < 0.001). Additionally, the central foveal thickness, the percentage of ellipsoid zone disruption, and the foveal avascular zone area were significantly lower in Group 1 than in Group 2 (all P < 0.005). Compared to Group 1, the vessel density (VD) and perfusion density of the foveal region was significantly increased in Group 2 (P < 0.001). In contrast, Group 2 showed significantly decreased VD in the parafoveal region compared with Group 1 (P < 0.05). Significant differences in OCTA parameters including ‘total number of junctions’, ‘junction density’, ‘total vessel length’, ‘average vessel length’, ‘total number of end points’ were observed between Group 1 and Group 2 (all P < 0.01). The foveal light sensitivity was significantly positively correlated with VD in the parafoveal region and negatively correlated with EIFL alteration, best-corrected visual acuity and ellipsoid zone disruption [Log(λ) = − 0.18303, λ = 0.6561]. Conclusions The presence of EIFL and decreased VD in the parafoveal region, factors that collectively elevate the risk of disease progression, are significantly and independently correlated with reduced microperimetric retinal sensitivity in patients with idiopathic ERM.